Boundedness in Lebesgue spaces of Riesz potentials on commutative hypergroups - Hajibayov, Mubariz (Global Journal of Mathematical Analysis, 2015)
In the present paper we consider Riesz potentials on commutative hypergroups and prove Â the boundedness of these potentials from \(L^p ( K,λ ) \) Â to \(L^q ( K,λ ) \). We also prove the Â inequality from \(L^1 ( K,λ ) \) to weak \(L^q ( K,λ ) \) for Riesz potentials on commutative hypergroups.